Resentment and aggression in 5th grade students - Obregón López, Giuliana Margarita (2017)
The following research was mainly aimed at establishing the correlation between resentmentand aggressiveness in 5th grade high school students of an Educational Institution in Lima. The employed standpoint was the quantitative and the method deductive hypothetical. We used two instruments with validity and reliability for data collection, which were the resentment scale of Leon and Romero, and the questionnaire of aggression of Buss and Perry (adapted to our environment by Matalinares). Regarding the statistical analysis, to establish the correlation coefficient of Pearson correlation in the results of the value of 0.257 was found * which indicates that there is significant positive correlation between the two variables was used as the p-value (sig ) is less than 0.05., so he concludes that having evaluated more resentment, tend to show higher levels of aggression